The flavonoid of Dracocephalum heterophyllum Benth. ameliorates cerebral small vessel disease by inhibiting the autophagy via Angs-Tie2 signaling pathway - Liu, Lin; He, Wen; Liu, Sijing; Li, Yang; Wang, Peng; Yan, Fang; Yang, Wenjing; Yang, Yongxue; Guo, Jinlin (Frontiers in Pharmacology, 2025)
BackgroundCerebral small vessel disease (CSVD) is a common cause of stroke and vascular cognitive impairment. It is urgent to find drugs targeting CSVD. This study explores the therapeutic potential of the flavonoid (DHBF) derived from Dracocephalum heterophyllum Benth., a traditional Tibetan medicine used for cardiovascular diseases, in treating CSVD and its underlying mechanisms.MethodsSpontaneously hypertensive rats (24-weeks-old) were treated with DHBF for 8 weeks. The Morris water maze test, laser speckle contrast imaging, photoacoustic tomography, HE and Nissl staining were used to evaluate the effect of DHBF in CSVD rats. Network pharmacology and UPLC-MS were used to identify DHBF components and potential mechanisms. Human umbilical vein endothelial cells (HUVECs) were exposed to 10% O2 to mimic CSVD conditions, and the effects of DHBF on proliferation, migration, and autophagy were evaluated. The expression levels of Angs, Tie2, LC3-Ⅱ/Ⅰ and p62 were detected by qRT-PCR and WB analyses. Molecular docking and lentivirus-mediated Ang2 knockdown/overexpression were performed to validate DHBF’s targeting of Ang2.ResultsDHBF alleviated vessel injury, improved learning and memory abilities, and increased cerebral blood perfusion and oxygen supply capacity in 24-week-old CSVD rats (p < 0.05). A total of 31 components of DHBF were identified by UPLC-Q-Orbitrap HRMS. Results indicated that DHBF alleviated CSVD by promoting cell proliferation, migration and invasion while inhibiting autophagy in endothelial cell. This regulation was associated with alterations in the Angs-Tie2 pathway and its downstream proteins, including decreased levels of Ang2, Tie2, LC3-Ⅱ/LC3-Ⅰ and increased the levels of Ang1 and p62 (p < 0.05). Knocking down Ang2 showed regulatory effects similar to those observed with DHBF intervention, while overexpression of Ang2 showed opposite effects. In addition, Ang2 overexpression attenuated the regulatory effects of DHBF on Angs-Tie2 pathways and autophagy in HUVECs. These results demonstrated that DHBF alleviated CSVD via inhibiting Ang2, which might be related to danshensu, lonicerin, 8-hydroxyquinoline, esculetin, isophorone, and ethyl caffeate.ConclusionIn summary, DHBF exerts a therapeutic effect on CSVD by inhibiting Ang2, regulating the Angs-Tie2 pathway, and inhibiting endothelial autophagy. This study proposed a potential effective target for CSVD, provided data to support subsequent drug development for this condition.